Joint decisions of machining process parameters setting and lot-size determination with environmental and quality cost consideration. (January 2018) - Awad, Mahmoud I.; Hassan, Noha M.
Highlights: Optimization model for a product-mix production considering cost, quality, and environmental impact is provided. Quality cost is modeled using a probabilistic version of Taguchi loss function of roughness of final products produced through turning process. Environmental cost adapts life cycle analysis and considers CO2 emission traded caps. Abstract: In today's highly competitive market, it is not enough to produce high quality products at lower costs but also sustainability has to be factored in the decision making process. The objective of this research is to propose an optimization model that considers both losses due to negative environmental impact and rework cost for a product-mix production planning problem manufactured through turning operation. The mathematical model solves simultaneously for the optimal production quantities and machining parameters that maximize the total expected profit. Surface roughness is used as a metric to assess the desired quality level of the finished machined part. Roughness was modeled as a random variable using normal distribution while rework cost was calculated in terms of probabilities of exceeding roughness target and upper tolerance limit. Energy consumption and CO2 emissions are estimated using lifecycle analysis (LCA) approach and used to quantify the environmental cost. A numerical example is used to illustrate the adequacy of model proposed through a turning study. Results revealed the importance of taking a system approach when solving for optimum machining parameters and lot-sizing if quality and environmental costs are considered. It was shown that a stringent quality cost target will drive process parameters such as feed and nose radius to lower values in order to minimize rework cost. Moreover, and in order for environmental cost to significantly impact decision makers, carbon selling price or cap limit needs to be stringent enough to drive emission reductions.